Copper‐Catalyzed Oxidative Synthesis of Sulfinamides Using Thiols or Disulfides with Amines. Issue 12 (5th April 2016) - Taniguchi, Nobukazu
Abstract: Copper‐catalyzed coupling of thiols with amines was used to synthesize numerous sulfinamides in excellent yields. Sulfenamides or sulfonamides were also formed as reaction byproducts albeit in trace quantities. The procedure is carried out as a one step and was found to be promoted by the addition of water and NH4 PF6 under aerobic conditions. Furthermore, the reaction proceeds smoothly when using disulfides. Consequently, it is clear that both thiols and disulfides are useful S‐sources under these reaction conditons. Abstract : Copper‐catalyzed coupling of thiols with amines affords an array of sulfinamides in excellent yields with accompanying traces of sulfenamides or sulfonamides. The one step procedure is promoted by water and NH4 PF6 in the presence of air. Additionally, the reaction using disulfides proceeds smoothly, highlighting that both thiols and disulfides are amenable to the reaction conditions.